The effect of Varenicline and Bupropion on smoking cessation: A network meta-analysis of 20 randomized controlled trials. (August 2022) - Guo, Kangle; Wang, Shizhong; Shang, Xue; E, Fenfen; Hou, Liangying; Li, Jieyun; Li, Yanfei; Yang, Kehu; Li, Xiuxia
Highlights: Seven interventions associated with Varenicline and Bupropion were compared in the network meta-analysis. Varenicline, Bupropion, and NRT monotherapy were superior to placebo for smoking cessation. A high credibility evidence supported that VAR+BUP had the greatest probability of becoming the best intervention. Abstract: Objective: A network meta-analysis (NMA) was conducted to investigate the effect of varenicline (VAR), bupropion (BUP), and nicotine replacement therapy (NRT) on smoking cessation. Methods: Eight databases were searched in May 2021, and only randomized controlled trials (RCTs) using varenicline, bupropion, or NRT (single or combined) for smoking cessation were included. The risk of bias in the included RCTs was assessed using the Cochrane Handbook tool. Stata 15.1 software was used to perform NMA, and the quality of the evidence was evaluated using Confidence in Network Meta-analysis (CINeMA). Findings: Twenty RCTs involving 16, 702 smokers were included. The risk of bias results showed that 10 RCTs were rated as high, three were low, and seven were unclear. A total of 21 pairs were compared based on seven interventions. The NMA showed that, compared to the placebo (PLA), the other six interventions had significant efficacy in smoking cessation, where VAR + BUP showed the best effect of all treatments (odds ratio (OR) = 6.08, 95% confidence interval (CI) [3.47, 10.66]). Moreover, VAR + BUP was superior to VAR + NRT (OR = 1.66, 95% CI [1.07, 2.59]) and the three monotherapies (VAR, BUP, and NRT). In the monotherapies, the results of pairwise comparisons of VAR, BUP, and NRT did not show significant differences. Finally, the surface under the cumulative ranking curve (SUCRA) value indicated that VAR + BUP had the greatest probability of becoming the best intervention. Conclusions: The efficacy of VAR, BUP, and NRT alone increased the odds of smoking abstinence better than the placebo, combined interventions were superior to monotherapy, and VAR combined with other interventions had a better smoking cessation effect.